Herradurichnus, Gyrochorte and Daedalus from the Balcarce Formation (Silurian of the Tandilia System, Argentina) revisited - Pazos, Pablo Jose (2016)
The Balcarce Formation is a tide-dominated unit outcropping in the TandiliaSystem which contains abundant ichnofossils firstly studied by Borrello (1966).Original assignments in the unit like Cruziana and Arthrophycus remainindisputable and suggest a Late Ordovician lower Silurian age. Conversely,others were later reassigned to other ichnogenera. In particular the materialreexamined in the field (Cabo Corrientes locality) received the attention ofPoiré and del Valle (1996) and Seilacher et al. (2003) that introduced newassignments (e.g. Arenicolites, Didymaulichnus, Diplichnites andDiplocraterion). Interestingly, some trace fossils present there were analyzedand also discussed or reassigned in these or other works, sometimesinformally (e.g. Heimdallia and Selenichnites). One unusual case is the materialoriginally assigned to Palaeophycus that was later reassigned to Scolicia,Gyrochorte or Heimdallia. Some field specimens (fig. 1) partially resembleArthrophycus brogniartii but differ in the variable course (winding, irregularor angularly meandering), subtriangular shape, variable width andasymmetrical ribs. These features do not fit in Arthrophycus and probablyneither in the other previously attributed ichnogenera. Herradurichnus isrecorded as the classical horse-shoe form, but also crescent and subtriangularin shape (fig. 2); variable incised forms suggest different producers thanxiphosuran-like animals, probably a worm-like animal. The horizontaldisplacement of the Daedalus examples resembles the activity of siphons (fig.3), like some sections of Hillichnus. Herradurichnus and Didymaulichnus arecross cut by Arthrophycus-like trace fossils. Finally, other trace fossils aremeniscate endichnial forms without walls and showing basal marks.